AB0683 Troponin Might be a Candidate Marker for Subclinical Scleroderma Heart Involvement (SHI): A Preliminary Report. (9th June 2015) - Stagnaro, C.; d'Ascanio, A.; Parma, A.; Conti, U.; Emdin, M.; Della Rossa, A.; Mosca, M.
Abstract : Background: Systemic sclerosis (SSc) is a rare connective tissue disease with pronounced alterations of the microvascular system, frequent cellular and humoral immunity abnormalities and fibroblast dysfunction. All these events result in an overproduction of collagen with possible involvement of skin and internal organs such as heart. Cardiac involvement is common in SSc; it may involve all of the heart structures. SHI can often be asymptomatic and insidious, although it is almost invariably associated with ominous outcome. For this reason it is essential to identify markers useful to early recognize any sort of SHI. Objectives: The aim of this study was to investigate if high sensitivity troponin (HSTn) could be a useful tool to identify subclinical SHI. Methods: For this purpose we analyzed data of 45 consecutive SSc patients (M:F =1:44; mean age 60 years, range 35-91 years; mean disease duration 10, 5 years; 22 with limited cutaneous SSc, 23 with diffuse cutaneous SSc) followed at our unit. Among all our SSc patients admitted in the last two years, we selected only those who underwent the following instrumental and laboratory investigations during the same hospitalization: electrocardiogram (ECG), echocardiogram and HSTn. Most of patients performed also N-terminal segment of proBNP (NT-proBNP) test and three patients underwent cardiac magnetic resonance imaging (cMRI). We excluded from our study patients with overt pulmonary arterial hypertension since it could alter cardiac markers. For one of the selected patients we collected data in more than one occasion. Furthermore we defined as SHI the presence of one or more of these conditions, in the absence of any other causes: diastolic dysfunction (at least grade II or grade I if patient is younger than 50 years or if it is also recognizable another cause of SHI), pericardial effusion, conduction abnormalities (bundle branch block or atrioventricular block) or arrhythmias, edema and/or T2 weighted non ischemic pattern showed by cMRI. Correlation between laboratory data and instrumental measurements were performed by non parametric tests for continuous variables and contingency tables for categorical variables (Stat-View, SAS). Fisher exact test was applied when indicated. Results: Among the analyzed patients 9 showed SHI and 16 and 19 had respectively high levels of HSTn and of NT-proBNP. SHI seems to be correlated with high levels of HSTn (p 0, 04) but not with high level of NT-proBNP. Moreover we observed that, among patients with abnormal NT-proBNP, 11 had also out of range HSTn (p 0, 009); the values of HSTn were strictly correlated (spearman rank correlation 0, 43, p<0, 006) Conclusions: Our data shows a close relationship between HSTn and NT-proBNP in SSc patients with cardiac involvement. However, if we consider these 2 serological parameters independently, we observe that HSTn might be a marker of SHI while NT-proBNP seems to be a less specific index of heart dysfunction. Since SHI is often subclinical, but anyway associated with a significantly increased morbidity and mortality, a serological marker would be very useful not only to early diagnose SHI but also to select patients who need further investigations such as cMRI. However further studies on a larger number of patients are necessary to confirm these preliminary results. Disclosure of Interest: None declared